Immigrants on welfare: Assimilation and benefit substitution - Tyra Ekhaugen (University of Oslo, Department of Economics, 2005)
Non-western immigrants in Norway are shown to rely heavily on welfare transfers for several years after immigration. While refugee immigrants assimilate slightly out of welfare, other non-western immigrants assimilate rapidly into welfare. Re-migration is selective for both non-western and western immigrants, insofar as the probability of re-migration correlates negatively with the probability of receiving welfare. We argue that previous studies may have reached biased estimates of welfare assimilation, both because they have disregarded the possibility of selective re-migration, and because they have focused only on social assistance, not taking into account the possibility of benefit substitution.
Keywords: F22; J61; 330; immigrants; immigration; re-migration; Einwanderung; Soziale Integration; Sozialhilfeempfänger; Sozialhilfe; Schätzung; Norwegen